Postcolonial identity in Yurii Andrukhovych’s poetry: landscapes and dislocation - Borysiuk, Iryna (Slavia Centralis, 2020)
Postcolonial theory deals with many important issues and the question of identity is a key one along with the power / knowledge dichotomy and the narrative strategies of representation. The analysis of literary text allows to identify ideological transformations in public discourse and individual consciousness which is based on subject’s linguistic behavior. The postcolonial approach allows to analyze identity construction and transformation as well as the intersection between the speaking subject and its different identities. In this context, the poetry of Yurii Andrukhovych is an interesting object for reflection. Subject construction and transformation strategies can be examined through the landscape and dislocation key concept. This transformation is vivid in the context of generational paradigm. Based on the transition from the 1980s generation, this poetry provides subject expansion to the 1990s generation poetry, and is oriented towards the doubling and multiplying of subject.
Keywords: postcolonial theory; identity; subjectivity; contemporary Ukrainian poetry; Yurii Andrukhovych